Sapropterin dihydrochloride for the treatment of hyperphenylalaninemias - Blau, Nenad (Expert opinion on drug metabolism & toxicology, 2013)
Introduction: Phenylketonuria (PKU) is caused by mutation of the enzyme, phenylalanine (Phe) hydroxylase (PAH). The hyperphenylalaninemia characteristic of PKU causes devastating neurological damage if not identified and treated at birth with a Phe-restricted diet. Sapropterin dihydrochloride, a pharmaceutical formulation of the natural cofactor for PAH (6R-tetrahydrobiopterin; BH4), is now available for the management of hyperphenylalaninemia in some PKU patients, including BH4 deficiencies. Sapropterin dihydrochloride improves dietary Phe tolerance in about 20% of patients with PKU. Areas covered: This evaluation describes the identification of patients suitable for treatment of sapropterin dihydrochloride, together with its indications, therapeutic properties and efficacy. Furthermore, the article reviews its safety and tolerability in patients with PKU or BH4 deficiency. Expert opinion: A reduction in blood Phe of at least 30% occurred in ∼ 20 - 30% of sapropterin-treated PKU patients (mostly with milder forms of PKU). Treatment with sapropterin resulted in clinically significant and sustained reductions in blood Phe concentrations and increased dietary Phe tolerance in well-designed clinical studies in PKU patients who responded to BH4. Successful treatment with sapropterin may lead to a relaxation of the Phe-restricted diet, although continued monitoring of blood Phe is required. Sapropterin was well tolerated.